Comparison of yellow dent and nutridense corn hybrids for nursery pig diets - Hastad, C.W.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 315 nursery pigs (initially 33.5 lb) were used in a 21-d growth assay to compare relative energy values of ‘Nutridense’ and ‘Nutridense Low Phytate’ corn compared to Yellow Dent corn. Dietary treatments consisted of a 3 × 3 factorial with three sources of corn with 0, 3, or 6% added fat. Increasing the energy density of the diet with added fat or higher energy corn varieties (Nutridense or Nutridense-LP corn) linearly improved feed efficiency. The linear improvement in feed efficiency allowed us to calculate the energy content of the Nutridense corn varieties relative to Yellow Dent corn. We determined that the ME values published by the University of Illinois indicating that Nutridense and Nutridense Low Phytate corn contain approximately 6.5 and 4% more energy, respectively, than normal Yellow Dent corn are appropriate for diet formulation.
Keywords: Swine; Corn; Fat; Energy; Nursery pigs